Vascular graft failure of leg arterial bypasses - a review - Richa Handa; Sanjiv Sharma (Journal of Hypertension and Cardiology, 2014)
This review discusses causes of lower‑limb bypass graft failure and strategies to improve durability. It considers patient selection, conduit choice, surveillance, and re‑intervention options.
Keywords: Graft failure